Shape memory alloys and their medical application - Tanikić, Dejan I.; Manić, Miodrag T.; Ranđelović, Saša S.; Brodić, Darko T. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Shape memory alloys - SMAs are specific materials which has the ability to change their shape and return to some memorized state, which is caused by the changes in their temperature. Because of their specificity and unusual characteristics, the area of usage of SMAs is very large and heterogeneous. SMAs are mostly biocompatible, which enables their usage in medicine. Some basic characteristics of the shape memory alloys, different types of their transformations, as well as some possibilities of their usage in medicine will be presented in this paper. Introduction The main characteristic of the shape memory alloys, their possibility to return to some remembered state, has been noticed on copper based alloys in the thirties of the last century. However, nitinol (nickel-titanium alloy), as one of the most used SMAs, was discovered at the end of the sixties of the last century. The first documented large usage of SMAs was in 1971 for a coupling to connect titanium hydraulic tubing in a Grumman F-14 aircraft. The large usage of SMAs for the production of valves in air condition systems was recorded in Japan in the eighties of the last century. The first usage of SMAs in the dental and medical fields was recorded at the same time. SMA functionality principles The main functionality principle of SMAs is explained by the solid state phase transition, called marthensitic thermoelastic transformation from the austenitic to the martensitic phase and vice-versa. One-way shape memory effect: In this case, material is firstly deformed at some lower temperature. Due to the one-way shape memory effect, the material can return to its memorized shape by simple heating. Two-way shape memory effect: The main characteristic of this effect is changing of the material shape by its alternately heating and cooling, without any external forces. Superthermoelastic effect: Some materials have the ability to accept extremely large loads and return to its original shape after unloading. This characteristic is known as superelasticity or pseudoelasticity. Superelastic effect: This effect happens at the constant temperature. This occurrence is similar to the classical elasticity, but the deformations of the superelastic materials are multiple times larger than the deformations of classic materials. Superthermic effect: Unlike the superelastic effect, this effect happens during loading with the constant external force. The changes in the material shape occur with the changes in the environment temperature, similar as in the case of the two-way shape memory effect. Biocompatibility and biofunctionality Two main demands which medical implants must fulfil are biocompatibility and biofunctionality. Biocompatibility means that the used implant material is non toxic, while biofunctionality provides smooth execution of all needed functions of the implant in the required period of time. There are many SMAs in the nature, the basis of most of them are Fe, Cu, Ag, Au, Mn... However, the most popular SMA is NiTi alloy, called nitinol, which shows good mechanical as well as biocompatibile characteristics. Applications in orthopedic surgery Metal plates are already widely used in orthopedic surgery. However, metal plates and other orthopedic devices made from shape memory alloys provide some new, quality possibilities. It is a well-known fact that bone healing is much better in cases when broken parts are pressed towards each other during healing. This external force can be obtained by using SMA plates. In this case, SMA plates are deformed at a lower temperature, and then applied onto the broken bone. After application, the plate is heated at the body temperature, which causes returning to the memorized shape, thus providing necessary force for broken parts to stick together. Dental applications Dental braces are medical devices that provide normal teeth growth and correction of the teeth disposition, using external forces obtained from the braces wires made from SMAs. Forces should not be too large because they can deform teeth, also they should not be too small because they will not be able to realize the main purpose. SMAs in braces enable constant and uniform external forces, which affects the teeth during a long period of time, avoiding the need for frequent dentist interventions. Cardiovascular applications SMA devices are commonly used in this medical field, resulting in avoiding classic operations which require total anaesthesia. The Simon filter is used for catching and holding clots of the blood stream, preventing the emboli in cases where a patient is unable to use anticoagulants. SMA stents are also very often used devices, the application of which is based on the shape memory effect. Stents enable constant fluid flow inpotentially dangerous zones. Surgery instruments and tools The modern surgery requires minimal damage of the tissue, which implies the tendency towards small, extremely precise instruments and tools. The ability of SMA instruments to remember very complicated shapes, as well as the superelastic effect, are very important characteristics that can upgrade surgical instruments. The shape memory basket, the application of which is very similar to the Simon filter, is often used for removing kidney or bladder stones. The other applications of SMA instruments are guidewires, catheters, instruments for laparoscopy, etc. Conclusion Good mechanical and physical characteristics of shape memory alloys as well as the ability to remember some previous shapes are widely used in almost all fields of science and engineering. Their biocompatibility is one of the crucial characteristics which classify them into the priority class of materials for biomedical usage. The first part of this work explains the one-way shape memory effect, the two-way shape memory effect, the superelastic effect and the superthermic effect. After that, some examples of the SMA applications in biomedicine are presented.